The potential for walkability to narrow neighbourhood socioeconomic inequalities in physical function: A case study of middle-aged to older adults in Brisbane, Australia. (March 2019) - Loh, Venurs HY; Rachele, Jerome N.; Brown, Wendy J.; Ghani, Fatima; Washington, Simon; Turrell, Gavin
Abstract: Residents of disadvantaged neighbourhoods have poorer physical function than their advantaged counterparts, although the reasons for this remain largely unknown. We examined the moderating effects of walkability in the relationship between neighbourhood disadvantage and physical function using 2013 cross-sectional data from 5115 individuals aged 46–72 living in 200 neighbourhoods in Brisbane, Australia. The relationship between neighbourhood disadvantage and physical function differed by levels of walkability: positive associations as levels of walkability increased for those living in more disadvantaged neighbourhoods, and no difference for those living in more advantaged neighbourhoods. Further work is required to better understand the underlying mechanisms. Highlights: Greater neighbourhood disadvantage was associated with poorer physical function. However, the magnitude of this association reduced as walkability increased. Walkability has the potential to narrow neighbourhood inequalities in physical function.